Characteristics of Congenital Fetal Abnormalities in Ulin General Hospital Banjarmasin, South Kalimantan - Hermin Sabaruddin; Robyanoor Ahyadi; Bambang Abimanyu; Ruth Widhiati; Hariadi Hariadi; Hardyan Sauqi; Hendri Aqmal (Berkala Kedokteran, 2025)
Congenital abnormalities are the leading cause of infant mortality and a significant contributor to child and adult morbidity. This study aims to analyze the characteristics and outcomes of fetuses with congenital abnormalities in a tertiary hospital. This study aims to determine the characteristics, influencing factors and a clearer picture of the prevalence and types of congenital abnormalities that occur at Ulin Banjarmasin Regional Hospital. This descriptive-retrospective study used secondary data from medical records collected between January 2022 and December 2024. A total of 85 congenital abnormalities were recorded over three years, with maternal ages ranging from 20 to 35 years, covering 58 (68.24%) cases. The majority of the mothers came from Tabalong Regency, South Kalimantan Province (n=19, 22.35%). Gestational age in the third trimester (>28 weeks) was found in 72 women (81.71%). The majority of respondents were multigravida (n=57, 67.06%). Caesarean section was the most common method of delivery (n=65, 76.47%). There were 51 respondents who had no history of congenital disease in the family (60.00%). The majority of respondents did not consume alcohol and smoke (n=79, 92.94% and n=75, 88.24%). Regarding folic acid consumption, 56 respondents (65.88%) did not consume it. The most common type of congenital disorder found was related to the nervous system with the largest proportion of 21 babies.